2016
DOI: 10.1088/0953-2048/29/6/065018
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Pd-intercalated charge-density-wave rare earth poly-tellurides RETen

Abstract: The interplay between magnetism and superconductivity is one of the dominant themes in the study of unconventional superconductors, such as high-T c cuprates, iron pnictides and heavy fermions 1-3 . In such systems, the same d-or f-electrons tend to form magnetically ordered states and participate in building up a high density of states at the Fermi level, which is responsible for the superconductivity. Charge-density-wave (CDW) is another fascinating collective quantum phenomenon in some low dimensional mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Single-crystal x-ray diffraction on the same crystals confirmed the increase in the b-axis lattice constant consistent with Pd atoms intercalating between the van der Waals bonded Te bilayer [14]. DFT calculations also show this to be the most favorable location for intercalation [12]. No surface Pd atoms were observed for low intercalations, presumably due to the high volatility of the Pd atoms upon cleaving at room temperature.…”
Section: Fig 1 Phase Diagram Taken Frommentioning
confidence: 70%
See 1 more Smart Citation
“…Single-crystal x-ray diffraction on the same crystals confirmed the increase in the b-axis lattice constant consistent with Pd atoms intercalating between the van der Waals bonded Te bilayer [14]. DFT calculations also show this to be the most favorable location for intercalation [12]. No surface Pd atoms were observed for low intercalations, presumably due to the high volatility of the Pd atoms upon cleaving at room temperature.…”
Section: Fig 1 Phase Diagram Taken Frommentioning
confidence: 70%
“…It was recently suggested that Pd-intercalated RTe 3 (R = rare earth element) might be such a model system [12][13][14]. Here we explicitly study the case R = Er.…”
mentioning
confidence: 99%
“…Also, it is worth noting that all measurements point to a truly incommensurate CDW in all members of the RTe 3 family, with no observation of a lock-in transition to a commensurate wavevector at low temperatures. 35,36 Polycrystalline samples of Pd x RTe 3 (R=Y, La, Pr, Sm, Gd, Tb, Dy, Ho, Er, Tm) have been reported previously 37 , and it was established that for high enough x, the material superconducts with T c ā‰ˆ2-3 K regardless of the chosen rare earth. Single crystal measurements have only previously been reported in Pd x HoTe 3 38 , and only the remnant of the first CDW transition was observed.…”
Section: Introductionmentioning
confidence: 86%
“…In some of these compounds the CDW transition temperature can be tuned to zero across a potential quantum critical point by intercalation or applying pressure, indicating that electronic correlations could be the main driving force behind the CDW transition [35]. Moreover, some of these materials become superconducting at low temperatures in the vicinity of the putative CDW quantum critical point [36][37][38]. One of our aims is to provide clear experimental signatures of an incommensurate 2k F CDW quantum phase transition, which would allow to settle the question if the incommensurate CDW transition in materials like NbSe 2 is driven by electronic correlations, or by a different mechanism, such as the coupling to phonons.…”
Section: Introductionmentioning
confidence: 99%